1989
DOI: 10.1073/pnas.86.17.6553
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl-conjugated oligonucleotides: synthesis, properties, and activity as inhibitors of replication of human immunodeficiency virus in cell culture.

Abstract: A family of oligonucleotides and phosphorothioate oligonucleotide analogues was synthesized with a cholesteryl group tethered at the 3'-terminal internucleoside link. This modification, introduced to enhance interaction of the polyanions with cell membranes, significantly increases the antiviral activity of the oligomers, as judged by inhibition of syncytia formation and expression of viral proteins p17, p24, and reverse transcriptase for human immunodeficiency virus 1 in Molt-3 cells. In the most favorable ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
130
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(132 citation statements)
references
References 20 publications
(20 reference statements)
2
130
0
Order By: Relevance
“…Many lipophilic molecules have been used to modify ODNs (470,471). However, among them, cholesterol is perhaps the best characterized and extensively studied in vivo (472)(473)(474). Unlike other lipophilic molecules, it has been shown that cholesteryl conjugation confers ODNs enhanced binding to lipoproteins and thereby improved cellular association and transport especially into liver tissue.…”
Section: Conjugation With Lipophilic Molecules-mentioning
confidence: 99%
See 1 more Smart Citation
“…Many lipophilic molecules have been used to modify ODNs (470,471). However, among them, cholesterol is perhaps the best characterized and extensively studied in vivo (472)(473)(474). Unlike other lipophilic molecules, it has been shown that cholesteryl conjugation confers ODNs enhanced binding to lipoproteins and thereby improved cellular association and transport especially into liver tissue.…”
Section: Conjugation With Lipophilic Molecules-mentioning
confidence: 99%
“…Conjugation with cholesterol can be integrated into the synthesis of ODNs using nucleoside derivatives (472,475,476). However, cholesterol can also be conjugated to post-synthetic ODNs with functionalities at ends.…”
Section: Conjugation With Lipophilic Molecules-mentioning
confidence: 99%
“…Cholesterol modification has been shown to increase both the cell association and activity of phosphodiester and phosphorothioate oligonucleotides (Boutorine et al, 1989;Letsinger et al, 1989;Boutorine et al, 1993;Krieg et al, 1993). These compounds have been shown to be taken up, at least in part, by the LDL receptor (de Smidt et al, 1991;Krieg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…An approach to circumvent these problems has been to covalently bind native (phosphodiester) or modified (phosphorothioate) oligonucleotides to phospholipid (Shea et al, 1990) or other hydrophobic residues (Kabanov et al, 1990;Saison-Behmoaras et al, 1991), including cholesterol (Boutorine et al, 1989;Letsinger et al, 1989;Krieg et al, 1993). Cholesterol modification has been shown to increase both the cell association and activity of phosphodiester and phosphorothioate oligonucleotides (Boutorine et al, 1989;Letsinger et al, 1989;Boutorine et al, 1993;Krieg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, CaCl 2 or cationic liposomes have been mostly used as transfection reagents. Additional exogenous delivery methods are based on the conjugation of the oligonucleotides to polylysine compounds (22) or to lipophilic groups, like cholesterol (23,24).…”
mentioning
confidence: 99%